The various operating conditions, harmonics effects and stability of thyristor controlled reactor - Uzunoglu, M; Kocatepe, C; Yumurtaci, R; Gülez, K (IEEE, 2000)
Recently, there has been a rapid increase in the use of thyristor controlled reactor (TCR) in the power system in recent years. TCRs cause to take place nonsinusoidal components in energy systems because of using power electronic elements within the TCRs. Any one of harmonic components of nonsinusoidal quantities can cause resonance in the system. In this paper, TCR's are studied for various working conditions and also as a harmonic source. In addition, system stability is studied in the case of nonsinusoidal quantities in the system.
Keywords: stability; harmonics; TCR; Computer Science